A high-speed lateral PIN polysilicon photodiode on standard bulk CMOS process. (March 2017) - Zou, Wanghui; Xia, Yu; Chen, Diping; Zeng, Yun
Highlights: A high-speed lateral PIN polysilicon photodiode based on standard bulk CMOS process. A bandwidth of over 20 GHz was observed with a device area of 50 × 50 μm 2. A responsivity of 46 mA/V under the reverse voltage of 10 V at 520 nm wavelength was demonstrated. Abstract: This paper reports a lateral PIN polysilicon photodiode on standard bulk complementary metal-oxidesemiconductor (CMOS) process for monolithically integrated high-speed optoelectronic integrated circuits (OEIC). A nominal undoped polysilicon as the photodetection area is intentionally created without introducing any process modification. With the device area of 50 × 50 μm 2, a measured responsivity of 46 mA/W and a quantum efficiency of 11% were observed under the reverse voltage of 10 V and the wavelength of 520 nm. A compact equivalent circuit model for the proposed lateral photodiode is built to analyze the frequency response, and a bandwidth of over 20 GHz was obtained from the measured data, which is to the best of our knowledge the largest bandwidth ever reported based on standard bulk CMOS process.